The Relation of Academic Stress, Parental Social Support, Gratitude and Psychological Well-Being of Students in Pandemic COVID-19 Era - Kusumawati, Indra; Pratisti, Wiwien Dinar; Prasetyaningrum, Juliani (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
The purpose of this study was to examine the relationship between academic stress, parental social support and gratitude for psychological well-being in college students during the Covid-19 pandemic. The study used a correlational quantitative approach with the population of undergraduate students at Muhammadiyah University of Surakarta. The sampling technique used is Proportional Random Sampling. The research instrument used a psychological well-being scale (Ryff's Psychological Well-Being scale), the Educational Stress for adolescents (ESSA) scale, the Parental Social Support Scale, and the Gratitude Scale. Analysis of the data obtained using multiple regression analysis using the Statistical Package for Social Sciences (SPSS) program. (1) there was a significant relationship between academic stress, parental social support, gratitude and psychological well-being, (2) there was a negative and significant relationship between academic stress and psychological well-being with an effective contribution of 5.98 %, (3) there is a positive and significant relationship between parental social support and psychological well-being with an effective contribution of 9.93%, (4) there is a positive and significant relationship between gratitude and psychological well-being with an effective contribution of 25.73%. It was concluded that the gratitude variable had a more dominant influence on the psychological well-being variable. In other words, the psychological well-being of students is spiritual in nature which shows closeness to Allah SWT. This is in accordance with one of the recommendations in Islam that being grateful makes it easier for a person to feel happy and psychologically wellbeing.